Theaflavins as a novel cross-linker quickly stabilize demineralized dentin collagen against degradation - Hang Liu (Nature Portfolio, 2021)
Abstract To investigate the ability of theaflavins (TF) from black tea to protect dentin collagen against enzymatic degradation via cross-linking effect under clinically relevant conditions. 10-µm-thick dentin films were microtomed from dentin slabs of human molars. Following demineralization, films or slabs were treated with TF at two concentrations (0.4% and 2%) for 30 s. A well-known collagen cross-linker grape seed proanthocyanidins (PA) was used as control. Collagen cross-linking interactions and stabilization against enzymatic degradation were investigated by Fourier transform infrared spectroscopy, weight loss, hydroxyproline release, and scanning/transmission electron microscopy. Data were analyzed by ANOVA, Tukey’s and Student’s T test (α = 0.05%). The results showed collagen cross-linking and stabilization efficacy was dependent on TF/PA concentrations. At 2.0%, TF and PA offered nearly full protection to collagen; at 0.4%, TF exhibited a significantly better collagen stabilization effect than PA (P < 0.05), while untreated collagen was completely digested. It’s concluded that TF cross-links dentin collagen within a clinically relevant time (30 s) and offers excellent collagen protection against enzymatic degradation, with efficacy comparable to or better than PA. The study supports the potential use of TF as a novel, promising collagen cross-linker for degradation resistant, long-lasting dentin bonding in composite restorations.